2002
DOI: 10.17221/3527-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Optical isomers of chloropropanediols: mechanisms of their formation and decomposition in protein hydrolysates

Abstract: Protein hydrolysates produced by hydrochloric acid hydrolysis were analysed for 3-chloropropane-1,2-diol and its enantiomers. It was found that (R)-3-chloropropane-1,2-diol and (S)-3-chloropropane-1,2-diol were present in the hydrolysates in equimolar concentrations. Model experiments with glycerol, triolein and soy lecithin heated with hydrochloric acid in solution showed that these materials were precursors of 3-chloropropane-1,2-diol and 2-chloropropane-1,3-diol and, as expected, yielded racemic 3-chloropro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 20 publications
1
19
0
3
Order By: Relevance
“…The other two proposals postulated the formation of an intermediate acyl oxonium or an epoxide before nucleophilic attack by the chloride ions. Our study showing the effect of acidity on the formation supports the direct nucleophilic substitution mechanism, which is considered as a plausible mechanism [22][23][24].…”
Section: Resultssupporting
confidence: 76%
“…The other two proposals postulated the formation of an intermediate acyl oxonium or an epoxide before nucleophilic attack by the chloride ions. Our study showing the effect of acidity on the formation supports the direct nucleophilic substitution mechanism, which is considered as a plausible mechanism [22][23][24].…”
Section: Resultssupporting
confidence: 76%
“…Presently, there are four proposed mechanisms (Fig. 3) all involving S N 2 nucleophilic attack by chloride ions, distinguished from each other based on either the nature of the substrate or the leaving group 8, 23–26. Two of the proposed mechanisms involve direct nucleophilic attack by the chloride ion at the glycerol carbon atoms carrying either an ester group (pathway a) or a protonated hydroxyl group (pathway b).…”
Section: Process‐induced Chloropropanol Estersmentioning
confidence: 99%
“…The presence of these compounds in foods is of concern because the results of toxicological studies showed that they could endanger human health (EC 2001, BfR 2007, EFSA 2008, Joint FAO/WHO 2008). Velíšek et al (1979Velíšek et al ( , 2002 and Davídek et al (1982) were the first to report the discovery of CPD esters together with other chloropropanols in acid hydrolysed proteins (Velíšek et al 1980;Velíšek 2009) and in a cultivar of processed foods . The most important precursors of chloropropanol esters identified in foods are fats derived from glycerol (glycerolipids) such as triacylglycerols, partial acylglycerols, glycerophospholipids, and chlorides either naturally present or added as sodium chloride.…”
mentioning
confidence: 99%